Therapeutic Potential of Mesenchymal Stem Cells for Postmastectomy Lymphedema: A Literature Review. Issue 1 (30th August 2020) - Chen, Kuo; Sinelnikov, Mikhail Y.; Reshetov, Igor V.; Timashev, Petr; Gu, Yuanting; Mu, Lan; Lu, Pengwei; Zhang, Yuanyuan
Abstract : Upper limb lymphedema is one of the most common complications after breast cancer surgery and radiotherapy. Despite various physical therapy and surgical options available, the impaired lymph fluid drainage may be progressive due to lymphatic vascular insufficiency making treatment more difficulty. Stem cell therapy provides a promising alternative in the treatment of various chronic diseases. The wide applicability of cell therapy has been reviewed throughout literature. This review provides an overview of recent progress in the therapeutic effect of adult stem cells for primary and secondary lymphedema after breast surgery in preclinical studies and clinical cases. We start with a brief introduction about the pathophysiological mechanisms of postmastectomy lymphedema. Regarding existing treatments, we systematically summarize the benefits and limitations of recent progress. Because of their multidirectional differentiation potential and growth factor secretion, stem cell therapy shows promising results in the management of light to severe lymphedema. Increasing evidences have demonstrated a noticeable reduction in postmastectomy lymphedema and increased lymph‐angiogenesis after specific stem cell therapy. Current data suggests that stem cell therapy in lymphedema treatment provides reversal of pathological reorganization associated with lymphedema progression. Finally, we propose potential strategies for overcoming the challenges in the development of multipotent progenitor cells for the treatment and prevention of lymphedema in clinical practice.